PERANCANGAN MODEL SISTEM INFORMASI BERBASIS WEB SERVICE DENGAN MEMANFAATKAN TEKNOLOGI XML-RPC (EXTENSIBLE MARKUP LANGUAGE – REMOTE PROCEDURE CALL) - Goldie Gunadi (Faktor Exacta, 2011)
Currently, Web Service technology became very popular in the enterprise, one of the main reasons is because the technology is able to integrate different applications in a more simple platform and able to rectify the shortcomings of conventional middleware. The use of Web services more and more service done to the process of exchanging data or information through the Internet. In this technology, Web services using XML technology to exchange data. A number of methods currently used to provide Web services is SOAP, XML-RPC, and REST. XML-RPC technology itself is widely used because it has a simpler architecture than other techniques. A number of programming languages can be used to implement XML-RPC, which one of them is the PHP language. With PHP, we can create a Web Service that is used to manipulate data or perform an information stored in a database management system (Database Management System). Key Words: Web Service, XML, XML-RPC, SOAP, PHP